ANALISA KEKUATAN KONSTRUKSI RAMP DOOR PADA DECK CARGO BARGE DENGAN METODE ELEMEN HINGGA (FINITE ELEMENT METHOD) - Angger Setyo Aji; Didik Hardianto (Fakultas Sains dan Teknologi Universitas Karimun, 2022)
Ramp door is a construction on a ship that serves to access the entry and exit of vehicles or cargo to be transported by a ship. To ensure that the ramp door can accept the load from these vehicles, a strength analysis of the ramp door construction will be carried out using FEM-based structural static analysis software. From the results of software testing, the maximum stress value occurs on the ramp door model 2 of 166.08 MPa and the minimum stress/stress value occurs on the ramp door model 3 of 117.36 MPa. The safety factor values of the three ramp door models analyzed meet the requirements according to the rules of the Indonesian Classification Bureau, namely the safety factor value for the ramp door model 1 is 2.02, the ramp door model 2 is 1.50 and the ramp door model 3 is 2, 13.